Utilization of Some Local Date Palm Cultivars in Production of Jam and Assessment of its Quality - Sulieman, Abdel Moneim E.; Elsiddig, Basmat I.; Elkhalifa, Elamin A. (Gezira Journal of Engineering and Applied Sciences, 2012)
The objective of the present work was to study the possibility of the production of jam from three local cultivars of dates, namely; Jawa, Gondaila and Kulma. The chemical, microbiological and sensory characteristics of date jams were determined. The analysis revealed relative increase of moisture content in Kulma date jam (KDJ) (54.62%) as compared with those of Jawa date jam (JDJ) and Gondaila date jam (GDJ) which were 51.09% and 47.94%, respectively. The ash content was 1.7%, 0.4%, and 0.5% in (JDJ), (GDJ) and (KDJ); respectively. The total soluble solids was 80.5%, 80.8% and 78% in (JDJ), (GDJ) and (KDJ); respectively. Reducing sugars were higher in (JDJ) (34.0%) when compared with those of (KDJ) and (GDJ) which were 31% and 24%; respectively. Titrable acidity was 0.4%, 0.32% and 0.37% in (JDJ), (GDJ) and (KDJ); respectively. The highest pH value was found in (GDJ) (4.7) as compared with (JDJ) and (KDJ) which were 4.39 and 4.22, respectively. The highest value of ascorbic acid was found in (KDJ) (220 mg/100g) as compared with (JDJ) and (GDJ) which were 150 and 176 mg/100g; respectively. On the other hand, the microbiological analysis of date jam samples revealed low levels of total microbial load. The sensory evaluation indicated high acceptability for all samples of date jams